Superhard alloy composition

By using regenerated carbide materials and metal binding agents to form carbide compositions, the problems of complex processes and high costs in the production of existing WC and tungsten products are solved, and high mechanical characteristics and low cost production results are achieved.

JP2025503741APending Publication Date: 2025-02-04HYPERION MATERIALS & TECHNOLOGIES INC +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024542345
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-22
Filing Date
2023-01-17
Publication Date
2025-02-04

AI Technical Summary

Technical Problem

When existing chemical methods produce WC and tungsten products, there is the use of chemically strong acids and salts, resulting in complex processes and high cost, and poor mechanical and chemical properties of regenerated carbide materials, limiting their application in the production of new tools.

Method used

Regenerated carbide materials are used to form a carbide composition by mixing metal bonding agents and non-sintered carbides, avoiding electrochemical treatments and improving mechanical properties, including hardness and fracture strength.

Benefits of technology

Mechanical and chemical properties that are the same or higher as pure carbide materials are achieved, while simplifying the production process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503741000002
    Figure 2025503741000002
  • Figure 2025503741000003
    Figure 2025503741000003
  • Figure 2025503741000001
    Figure 2025503741000001
Patent Text Reader

Abstract

A hardmetal composition is provided that includes a carbide phase that includes a recycled carbide material in an amount greater than 70% by weight of the hardmetal composition. The hardmetal composition further includes a binder phase. The recycled carbide material includes about 45% to about 100% by weight of recycled zinc carbide. The hardmetal composition does not include any electrochemically processed recycled material. The hardmetal composition has comparable or superior mechanical properties, such as hardness, fracture toughness, transverse fracture strength, etc., when compared to a reference material that includes only virgin raw material. Additionally, methods of manufacturing sintered hardmetal articles, as well as cutting tools or cutting tool blanks, using the provided hardmetal compositions are provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001]

[0001] The present disclosure relates to hardmetal compositions including reclaimed carbide materials, which may include one or more of reclaimed zinc carbide and reclaimed unsintered carbide. [Background technology]

[0002]

[0002] Currently, several processes are used to recycle WC and tungsten products. These processes may include, for example, zinc process, cold stream process, alkaline leaching process, chlorination system, electrolysis, high temperature smelting, etc. Except for zinc process and cold stream process, other chemical methods include multiple conversion steps, extraction steps, and precipitation steps that increase cycle time and cost. Many of these chemical methods are undesirable because they involve the use and exposure of chemically strong acids, bases, and various inorganic salts.

[0003]

[0003] U.S. Patent No. 10,940,538, which is incorporated herein by reference in its entirety, describes a sintered cemented carbide article having a carbide phase and a binder phase. The carbide phase is present in an amount of at least 70 weight percent of the article. Notably, the carbide phase includes electrochemically treated cemented carbide scrap in an amount of 60-90 weight percent of the carbide phase, with the remainder being zinc treated carbide scrap and / or ammonium paratungstate treated cemented carbide scrap. According to U.S. Patent No. 10,940,538, the electrochemically treated cemented carbide scrap is utilized in high concentrations because other reclaimed or recycled carbide materials are said to have inferior chemical and mechanical properties, limiting the use of reclaimed or recycled carbide compositions in the manufacture of new tools.

[0004]

[0004] However, as described herein, unexpectedly, the present disclosure provides cemented carbide compositions that have mechanical and chemical properties (including, for example, hardness, fracture toughness, and transverse rupture strength) that are comparable to or superior to the articles described in U.S. Patent No. 10,940,538 that require the use of electrochemically processed cemented carbide scrap, as well as other carbide compositions that contain 100% virgin carbide material as the carbide phase. As a result, the realization of carbide compositions with superior chemical and mechanical properties that do not require cumbersome electrochemical recycling process steps provides an advantageous improvement over previously known solutions. Summary of the Invention

[0005]

[0005] A hardmetal composition is provided that includes or consists of a carbide phase and a binder phase. The carbide phase may be present in an amount of at least 70% by weight of the hardmetal composition. The carbide phase may include or consist of about 45% to about 100% by weight of recycled zinc carbide, based on the total weight of the carbide phase. The resulting hardmetal may have a transverse rupture strength (TRS-B) of at least about ≧3000 MPa, as measured according to the ISO 3327-2009 standard. Alternatively, the resulting hardmetal may exhibit a transverse rupture strength in the range of about 320 Ksi to about 570 Ksi, as measured according to the ASTM B 406 standard for a sample containing 100% by weight of recycled unsintered hardmetal. In some examples, the transverse rupture strength ranges from about 330 Ksi to about 540 Ksi when measured in accordance with ASTM B 406 for samples containing 90% by weight recycled zinc carbide and 10% by weight recycled non-sintered carbide. Transverse rupture strength ranges when measured in accordance with ASTM B 406 have also been demonstrated for samples defined as at least 80% by weight recycled zinc carbide and 20% by weight recycled non-sintered carbide, 70% by weight recycled zinc carbide and 30% by weight recycled non-sintered carbide, 60% by weight recycled zinc carbide and 40% by weight recycled non-sintered carbide, 50% by weight recycled zinc carbide and 50% by weight recycled non-sintered carbide, and 45% by weight recycled zinc carbide and 55% by weight recycled non-sintered carbide.

[0006] According to the ISO 3327-2009 standard, the transverse fracture strength (TRS-B) is generated by the maximum stress experienced by the cemented carbide composition before the moment of fracture in the transverse fracture strength test. The carbide phase of the cemented carbide composition may comprise or consist of tungsten carbide. Furthermore, the cemented carbide composition may be free of electrochemically processed recycled materials. As provided, the cemented carbide composition exhibits superior or at least substantially equivalent hardness, fracture toughness, and transverse fracture strength compared to a reference material composed of 10 wt. % Co and 90 wt. % virgin WC, or a cemented carbide material comprising.

[0007]

[0007] A method for producing a sintered hardmetal article is also provided. The method includes providing a carbide composition comprising or consisting of a carbide phase and a binder phase. The carbide phase may be present in an amount of at least 70% by weight of the hardmetal composition. The carbide phase may comprise or consist of about 45% to about 100% by weight of recycled zinc carbide, based on the total weight of the carbide phase. The binder phase may comprise or consist of a metal binder. The binder phase may comprise or consist of a metal binder. The powder blend may be subjected to a forming operation to form a green body. The green body may be subjected to a sintering operation to form a sintered hardmetal article. The resulting sintered hardmetal article may have a transverse rupture strength (TRS-B) of at least about ≧3000 MPa, as measured by ISO 3327-2009 standard. Alternatively, the resulting cemented carbide may have a transverse rupture strength in the range of about 320 Ksi to about 570 Ksi when measured according to ASTM B 406 on a sample containing 100% by weight recycled unsintered cemented carbide. In some examples, the transverse rupture strength is in the range of about 330 Ksi to about 540 Ksi when measured according to ASTM B 406 on a sample containing 90% by weight recycled zinc carbide and 10% by weight recycled unsintered carbide. Transverse breaking strength ranges, as measured in accordance with the ASTM B 406 standard, were similarly obtained for compositions specified as at least 80% by weight recycled zinc carbide and 20% by weight recycled non-sintered carbide, 70% by weight recycled zinc carbide and 30% by weight recycled non-sintered carbide, 60% by weight recycled zinc carbide and 40% by weight recycled non-sintered carbide, 50% by weight recycled zinc carbide and 50% by weight recycled non-sintered carbide, and 45% by weight recycled zinc carbide and 55% by weight recycled non-sintered carbide.

[0008]

[0008] Also provided is a cutting tool or a blank for a cutting tool. The cutting tool or blank for a cutting tool may comprise or consist of the carbide composition described hereinabove. The cutting tool or blank for a cutting tool may be manufactured as an article according to the method described hereinabove.

[0009]

[0009] Other systems, methods, features, and advantages will become apparent to one of ordinary skill in the art upon examination of the following figures and detailed description. All such additional systems, methods, features, and advantages are intended to be included in this specification, be within the scope of this disclosure, and be protected by the following claims. Nothing in this section should be construed as limiting those claims. Further aspects and advantages are described below in conjunction with the embodiments of the disclosure. It is understood that both the foregoing general description and the following detailed description of the disclosure are examples and explanations, and are intended to provide further explanation of the claimed disclosure.

[0010]

[0010] The accompanying drawings are included to provide a further understanding of the subject matter, are incorporated in and constitute a part of this specification, illustrate implementations of the subject matter, and together with the description, serve to explain the principles of the disclosure. [Brief description of the drawings]

[0011] [Figure 1A]

[0011] A graphical representation of hardness HV30 and fracture toughness Klc of a reference material composed of 10 wt. % Co and 90 wt. % virgin WC (upper circular dot indicates hardness HV30 and lower circular dot indicates fracture toughness Klc) and a material in accordance with the present subject matter (i.e., a material that includes recycled non-sintered carbide material with the remainder being recycled zinc carbide used as the balance to reach a total of 100 wt. % (HV30, dotted graph; Klc, dashed graph)). [Figure 1B]

[0012] 1 is a graphical representation of the TRS-B transverse rupture strength measured in accordance with the ISO 3327-2009 standard (dashed line graph) for a reference material consisting of 10 wt. % Co and 90 wt. % virgin WC (circled dots) and a material in accordance with the present inventive subject matter (i.e., recycled zinc carbide including recycled non-sintered carbide material, the remainder being used as the balance to reach a total of 100 wt. %). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012]

[0013] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the currently described subject matter pertains.

[0013]

[0014] When a range of values, e.g., a concentration range, a percentage range, a ratio range, is presented, it is understood that the upper and lower limits of that range, and any other stated or intervening value within that range, to the tenth of the lower limit, are included in the described subject matter, unless the context clearly dictates otherwise. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges, and such embodiments are also encompassed within the described subject matter, subject to any specifically excluded limit in the described range. When a described range includes one or both of the limits, ranges excluding either or both of those included limits are also included in the described subject matter.

[0014]

[0015] The following definitions set forth the parameters of the subject matter being described.

[0015]

[0016] As used herein, "wt. %" refers to a given weight percent of (i) the total weight of the cemented carbide composition, (ii) the total weight of the sintered article, (iii) the total weight of the carbide phase, or (iv) the total weight of the powder composition, unless specifically indicated otherwise. When "wt. %" is mentioned in the disclosure or claims, it is also explicitly mentioned whether it refers to a specific weight percent of (i), (ii), (iii), or (iv) in each scenario. A given wt. % refers to the wt. % of reclaimed unsintered carbide, and reclaimed zinc carbide, metal binder, and / or grain growth inhibitors may be used as the balance so that the total of (i), (ii), (iii), or (iv) equals 100 wt. %.

[0016]

[0017] The term "D50" as used herein refers to the particle size corresponding to when 50% of the volume of the sample particles are smaller than the stated D50 value and 50% of the volume of the sample particles are larger than the stated D50 value.

[0017] Similarly, the term "D90" as used herein refers to the particle size corresponding to when 90% of the volume of the sample particles are smaller than the stated D90 value and 10% of the volume of the sample particles are larger than the stated D90 value.

[0017] The term "D10" refers to the particle size corresponding to when 10% of the volume of the sample particles are smaller than the stated D10 value and 90% of the volume of the sample particles are larger than the stated D10 value. The width of the particle size distribution can be calculated by determining the span, which is defined by the formula (D90-D10) / D50. The span indicates how far apart the 10th and 90th percentage points are normalized to the midpoint.

[0017]

[0018] To determine the average grain size from a given grain size distribution, the skilled person will be readily familiar with the ISO 4499-2:2008 standard, which provides guidelines for the measurement of grain size in hard metallurgical alloys by metallographic techniques using optical or electron microscopy. It is intended to cover sintered WC / Co hard metals, which mainly contain WC as hard phase. It is also intended to measure the grain size and distribution by the linear intercept method.

[0018]

[0019] To further supplement the ISO 4499-2:2008 standard, those skilled in the art should also be aware of the ASTM B390-92(2006) standard, which is typically used to visually compare and classify the apparent grain size and distribution of cemented tungsten containing cobalt as a metallic binder in the binder phase.

[0019]

[0020] Cemented carbide grades can be classified according to the particle size of the carbide. Different types of grades are defined as nano, ultrafine, submicron, fine, medium fine, medium coarse, coarse, and very coarse. As used herein, the terms (I) "nano grade" is defined as material with a particle size of less than about 0.2 μm, (II) "ultrafine grade" is defined as material with a particle size of about 0.2 μm to about 0.5 μm, (III) "submicron grade" is defined as material with a particle size of about 0.5 μm to about 0.9 μm, and (IV) "fine grade" is defined as material with a particle size of about 1.0 μm to about 1.3 μm. (V) "medium coarse grade" is defined as material having a particle size of about 1.4 μm to about 2.0 μm, (VI) "medium coarse grade" is defined as material having a particle size of about 2.1 μm to about 3.4 μm, (VII) "coarse grain" is defined as material having a particle size of about 3.5 μm to about 5.0 μm, and (VIII) "very coarse grain" is defined as material having a particle size greater than about 5.0 μm.

[0020]

[0021] As used herein, the term "about" is intended to mean plus or minus 5% of the numerical values ​​used in the claims and the specification. Thus, "about" can be used to provide flexibility in the endpoints of a numerical range, where a particular value may be "above" or "below" a particular value. Therefore, for example, a value of 50% can be expressed as, for example, 47.5% to 52.25%, 47.5% to 52.5%, 47.75% to 50%, 50% to 52.5%, 48% to 48.5%, 48% to 48.75%, 48% to 49%, 48% to 49.5%, 48% to 49.75%, 48% to 50%, 48% to 50.25%, 48% to 50.5%, 48% to 50.75%, 48% to 51%, 48% to 51.5%, 48% to 51.75%, 48% to 52%, 48% to 52.25%, 48% to 52.5% , 48.25%~48.5%, 48.25%~48.75%, 48.25%~49%, 48.25%~49.5%, 48.25%~49.75%, 48.25%~50%, 48.25%~50.25%, 48.25%~50.5%, 48.25%~50.75%, 48.25%~51%, 48.25%~51.25%, 48.25%~51.5%, 48.25%~51.75%, 48.25%~52%, 48.25%~52.25%, 48.25%~52.5%, 48.5%~ 48.75%, 48.5%~49%, 48.5%~49.5%, 48.5%~49.75%, 48.5%~50%, 48.5%~50.25%, 48.5%~50.5%, 48.5%~50.75%, 48.5%~51%, 48.5%~51.25%, 48.5%~51.5%, 48.5%~51.75%, 48.5%~52%, 48.5%~52.25%, 48.5%~52.5%, 49%~49.25%, 49%~49.5%, 49%~49.75%, 49%~50%, 4 9%~50.25%, 49%~50.5%, 49%~50.75%, 49%~51%, 49%~51.25%, 49%~51.5%, 49%~51.75%, 49%~52%, 49%~52.25%, 49%~52.5%, 49.5%~49.75%, 49.5%~50%, 49.5%~50.25%, 49.5%~50.5%, 49.5%~50.75%, 49.5%~51%, 49.5%~51.5%, 49.5%~51.75%, 49.5%~52%, 49.5%~52.25%, 49.5%~52.5%, 49.75%~50%, 49.75%~50.25%, 49.75%~50.5%, 49.75%~50.75%, 49.75%~51%, 49.75%~51.25%, 49.75%~51.5%, 49.75%~51.75%, 49.75%~52%, 49.75%~ The ranges defined by ranges such as 52.25%, 49.75%-52.5%, 50%-50.25%, 50%-50.5%, 50%-50.75%, 50%-51%, 50%-51.25%, 50%-51.5%, 50%-52%, 50%-52.25%, 50%-52.5%, etc.

[0021]

[0022] As used herein, the term "predominantly" means to include at least 95% of a particular entity.

[0022]

[0023] As used herein, the term "green body" refers to a compacted material in the form of a compressed powder or compacted plate before the material is sintered.

[0023]

[0024] As used herein, "regenerated carbide material" means carbide material that has been recycled or regenerated in accordance with known methods. Regenerated carbide materials include regenerated zinc carbide, regenerated unsintered carbide, and the like.

[0024]

[0025] As used herein, "regenerated zinc carbide" refers to carbide that has been regenerated through a zinc recycling or regeneration method. For example, zinc regeneration of hard metal materials involves a process that uses molten zinc. In this process, the hard metal material is mixed with zinc ingots in a tray, and the mixture is heated in a furnace to liquefy the zinc. The liquefied zinc infiltrates the WC material and reacts with the metal binder in the carbide material. The zinc is then volatilized to leave porous WC, which is eventually ground into a powder.

[0025]

[0026] As used herein, "reclaimed non-sintered carbide" refers to reclaimed or salvaged non-sintered carbide material. Reclaimed non-sintered carbide includes soft recycled carbide material obtained from previously used non-sintered carbide powder or from scrap leftovers from carbide pressing and green fabrication processes. Thus, the distinct difference between reclaimed zinc carbide and reclaimed non-sintered carbide is that no chemical processing has been done to obtain the soft reclaimed non-sintered carbide for reuse.

[0026]

[0027] The term "transverse rupture strength" as used herein is a material property defined as the stress of a material just before the material yields in a flexure test. The transverse flexure test is most frequently used, where a test specimen with, for example, a chamfered circular or rectangular cross section is bent until it breaks or yields using a three-point bend test technique. The transverse rupture strength represents the maximum stress that occurs in a material just before the moment of yield. It is measured in terms of stress.

[0027]

[0028] As used herein, the term "virgin raw material" generally refers to material that has not previously been part of a sintered charcoal composition and has not been recycled, as opposed to recycled charcoal material.

[0028]

[0029] As used herein, the term "Palmqvist fracture toughness", i.e., K lc refers to the ability of a pre-cracked material to resist further fracture propagation upon absorbing energy.

[0029]

[0030] As used herein, the term "HV30 Vickers hardness" (i.e., applying a load of 30 kgf) is a measure of the resistance to localized plastic deformation and is obtained by indenting a sample with a Vickers tip at 30 kgf.

[0030]

[0031] The ISO 28079-2009 standard used herein specifies a method for measuring the fracture toughness and hardness of cemented carbides, cermets, and hard metals at room temperature by indentation. The ISO 28079-2009 standard applies to the measurement of fracture toughness and hardness calculated using the indentation and the diagonal length of the crack emanating from the indentation for Vickers hardness, and is intended for use with metal-bonded carbides and carbonitrides (e.g., cemented carbides, cermets, or hard metals). The test procedure proposed in the ISO 28079:2009 standard is intended for use at ambient temperatures, but can be extended to higher or lower temperatures by agreement. The test procedure proposed in the ISO 28079:2009 standard is also intended for use in normal laboratory air environments. It is not generally intended for use in corrosive environments such as strong acids or seawater. The ISO 28079-2009 standard is directly comparable to the ASTM B771 standard, e.g., as set forth on page 312 of the "Comprehensive Hard Materials book," 2014, Elsevier Ltd., the entire text of which is incorporated herein by reference. Thus, it can be assumed that fracture toughness and hardness measured using the ISO 28079-2009 standard are the same as those measured using the ASTM B771 standard.

[0031]

[0032] The ISO 3327-2009 standard used herein specifies a method called the flexural strength test for measuring the flexural strength of hard metals. The method is performed by placing a test specimen of a specified length, with a circular or beveled rectangular cross section, on two supports and applying a load in the middle until fracture occurs. The transverse fracture strength is determined as the average of several observations. The transverse fracture strength, also called the "modulus of rupture", "flexural strength" or "flexural strength", is a material property defined as the stress of a material just before it yields or breaks in a transverse fracture strength test. The transverse fracture strength therefore represents the maximum stress occurring in the material just before the moment of yielding. The method can be applied to hard metals with negligible ductility. When used for hard metals that exhibit significant plastic deformation before fracture, erroneous results may be obtained. In such cases, the method can be used only for comparative purposes. In general, the strength values ​​of type B specimens are approximately 10% to 20% higher than those obtained with type A specimens, depending on the material being tested and with the same surface condition. The repeatability is similar for all types of specimens. Type C specimens give strength values ​​approximately 5%-10% higher than Type B specimens, but the increase in strength values ​​is material related.

[0032]

[0033] The ASTM B 406 standard used herein specifies a method for measuring the transverse fracture strength of cemented carbide, where a specimen of cemented carbide is ground to the following specific dimensions: 0.200+ / -0.010 inch (5.00+ / -0.25 mm) thickness, 0.250+ / -0.010 inch (6.25+ / -0.25 mm) width, and 0.750 inch (19.0 mm) length. A load is applied to the following three-point fixture: (i) two ground carbide cylinders 0.250 + / - 0.001 inch (6.35 + / - 0.02 mm) in diameter, at least 0.500 inch (13 mm) in length, with parallel major axes and centers spaced 0.563 + / - 0.005 inch (14.3 + / - 0.1 mm) apart, and (ii) a movable member (i.e., substantially free to move only in a line perpendicular to the plane established by the axes of the two cylinders) with a carbide ball of dimensions 0.4 + / - 0.05 inch (10 + / - 1.3 mm), or a ground carbide cylinder with the same dimensions as the aforementioned cylinders and an axis parallel to the aforementioned cylinders.

[0033]

[0034] As used herein, the term "Weibull modulus" refers to a dimensionless parameter of the Weibull distribution, which is used to describe the variability of the measured transverse rupture strength of cemented carbide materials.

[0034]

[0035] As used herein, the term "superabrasive ultrahard material" or simply used interchangeably, the term "superabrasive material" refers to, but is not limited to, single crystal diamond, polycrystalline diamond (PCD), thermally stable polycrystalline diamond (PCD), chemical vapor deposition (CVD) diamond, metal matrix diamond composite, ceramic matrix diamond composite, nanodiamond, cubic boron nitride (cBN), polycrystalline cubic boron nitride (PCBN), or materials contained in combination with superabrasives or other superabrasives used in superabrasive cutting elements.

[0035]

[0036] As used herein, "physical vapor deposition (PVD)" refers to a variety of vacuum deposition techniques that can be used to produce thin films and coatings. PVD is characterized by a process in which the deposited material passes from a condensed phase to a gas phase and then back again to a thin film condensed phase. The most common PVD processes are sputtering and evaporation.

[0036]

[0037] As used herein, "chemical vapor deposition (CVD)" refers to a process in which a substrate (i.e., a hardmetal composition or hardmetal product) is exposed to one or more volatile precursors that react and / or decompose at the substrate surface to produce a desired deposit. Volatile by-products are frequently also produced, which are removed by the flow of gas through a reaction chamber.

[0037]

[0038] As used herein, the term "substantially" refers to the complete or nearly complete extent or degree of an action, property, characteristic, state, structure, item, or result.

[0038]

[0039] As used throughout this disclosure, the term "generally" has the meaning of "approximately," "typically," "approximately," or "in the vicinity or range."

[0039]

[0040] As used herein, "spherical" refers to particles having a substantially "round" shape.

[0040]

[0041] The present disclosure arises from the concept of demonstrating a surprising, novel and original solution over the prior art by producing a hardmetal composition comprising (i) recycled zinc carbide and (ii) recycled non-sintered carbide. The hardmetal composition does not contain any electrochemically processed recycled material. This provides the advantage of improved or at least comparable mechanical properties of hardness, fracture toughness and transverse fracture strength when compared to a hardmetal used as a reference material comprising only virgin raw materials. This results in an advantageous improvement over the previously known solutions due to the elimination of the cumbersome electrochemical recycling process step.

[0041]

[0042] In one aspect, a hardmetal composition is provided that includes a carbide phase (or carbide material) that can generally include regenerative carbide material in an amount greater than 70% by weight of the hardmetal composition. The carbide phase may alternatively be present in an amount greater than 75% by weight of the cemented carbide composition, greater than 80% by weight of the cemented carbide composition, greater than 85% by weight of the cemented carbide composition, greater than 89% by weight of the cemented carbide composition, greater than 90% by weight of the cemented carbide composition, greater than 95% by weight of the cemented carbide composition, about 70% to about 95% by weight of the cemented carbide composition, about 70% to about 90% by weight of the cemented carbide composition, about 75% to about 95% by weight of the cemented carbide composition, about 70% to about 95% by weight of the cemented carbide composition, about 80% to about 95% by weight of the cemented carbide composition, about 80% to about 90% by weight of the cemented carbide composition, about 85% to about 95% by weight of the cemented carbide composition, or about 85% to about 90% by weight of the cemented carbide composition.

[0042]

[0043] The carbide phase may include or consist of recycled zinc carbide, recycled unsintered carbide, virgin carbide, ammonium paratungstate treated cemented carbide scrap, among other carbide materials.

[0043]

[0044] The regenerator zinc carbide material may be present in the carbide phase in an amount of about 45% to about 100% by weight based on the weight of the carbide phase, about 45% to about 95% by weight based on the weight of the carbide phase, about 45% to about 90% by weight based on the weight of the carbide phase, about 45% to about 85% by weight based on the weight of the carbide phase, about 45% to about 80% by weight based on the weight of the carbide phase, about 45% to about 75% by weight based on the weight of the carbide phase, about 45% to about 70% by weight based on the weight of the carbide phase, or about 45% to about 65% by weight based on the weight of the carbide phase. % by weight based on the weight of the carbide phase, about 50% by weight to about 100% by weight based on the weight of the carbide phase, about 50% by weight to about 95% by weight based on the weight of the carbide phase, about 50% by weight to about 90% by weight based on the weight of the carbide phase, about 50% by weight to about 85% by weight based on the weight of the carbide phase, about 50% by weight to about 80% by weight based on the weight of the carbide phase, about 50% by weight to about 75 ... 0% to about 70% by weight, about 50% to about 65% by weight based on the weight of the carbide phase, about 55% to about 100% by weight based on the weight of the carbide phase, about 55% to about 95% by weight based on the weight of the carbide phase, about 55% to about 90% by weight based on the weight of the carbide phase, about 55% to about 85% by weight based on the weight of the carbide phase, about 55% to about 80% by weight based on the weight of the carbide phase, about 55% by weight based on the weight of the carbide phase about 75% by weight, about 55% by weight to about 70% by weight based on the weight of the carbide phase, about 55% by weight to about 65% by weight based on the weight of the carbide phase, about 60% by weight to about 100% by weight based on the weight of the carbide phase, about 60% by weight to about 95% by weight based on the weight of the carbide phase, about 60% by weight to about 90% by weight based on the weight of the carbide phase, about 60% by weight to about 85% by weight based on the weight of the carbide phase, about 60% by weight to about 80% by weight based on the weight of the carbide phase %, about 60% to about 75% by weight based on the weight of the carbide phase, about 60% to about 70% by weight based on the weight of the carbide phase, about 55% to about 65% by weight based on the weight of the carbide phase, about 60% to about 100% by weight based on the weight of the carbide phase, about 60% to about 95% by weight based on the weight of the carbide phase, about 60% to about 90% by weight based on the weight of the carbide phase, about 60% to about 85% by weight based on the weight of the carbide phase,about 60% by weight to about 80% by weight based on the weight of the carbide phase, about 60% by weight to about 75% by weight based on the weight of the carbide phase, about 60% by weight to about 70% by weight based on the weight of the carbide phase, about 60% by weight to about 65% by weight based on the weight of the carbide phase, about 70% by weight to about 100% by weight based on the weight of the carbide phase, about 70% by weight to about 95% by weight based on the weight of the carbide phase, about 70% by weight to about 90% by weight based on the weight of the carbide phase, about 70% by weight to about 85% by weight based on the weight of the carbide phase, about 70% by weight to about 80% by weight based on the weight of the carbide phase, about 70% by weight to about 70% by weight based on the weight of the carbide phase 5% by weight, about 75% to about 100% by weight based on the weight of the carbide phase, about 75% to about 95% by weight based on the weight of the carbide phase, about 75% to about 90% by weight based on the weight of the carbide phase, about 75% to about 85% by weight based on the weight of the carbide phase, about 75% to about 80% by weight based on the weight of the carbide phase, about 80% to about 100% by weight based on the weight of the carbide phase, about 80% to about 95% by weight based on the weight of the carbide phase, about 80% to about 90% by weight based on the weight of the carbide phase, or about 80% to about 85% by weight based on the weight of the carbide phase.

[0044]

[0045] The regenerated non-sintered carbide material may be about 0% to about 5% by weight based on the weight of the carbide phase, about 0% to about 10% by weight based on the weight of the carbide phase, about 0% to about 20% by weight based on the weight of the carbide phase, about 0% to about 30% by weight based on the weight of the carbide phase, about 0% to about 35% by weight based on the weight of the carbide phase, about 0% to about 40% by weight based on the weight of the carbide phase, about 0% to about 45% by weight based on the weight of the carbide phase, about 5% to about 10% by weight based on the weight of the carbide phase, about 5% to about 20% by weight based on the weight of the carbide phase, about 5% to about 30% by weight based on the weight of the carbide phase, about 5% to about 35% by weight based on the weight of the carbide phase, about 5% to about The carbide phase may be present in an amount of about 40% by weight, about 5% by weight to about 45% by weight based on the weight of the carbide phase, about 10% by weight to about 20% by weight based on the weight of the carbide phase, about 10% by weight to about 30% by weight based on the weight of the carbide phase, about 10% by weight to about 35% by weight based on the weight of the carbide phase, about 10% by weight to about 40% by weight based on the weight of the carbide phase, about 10% by weight to about 45% by weight based on the weight of the carbide phase, about 15% by weight to about 20% by weight based on the weight of the carbide phase, about 15% by weight to about 30% by weight based on the weight of the carbide phase, about 15% by weight to about 35% by weight based on the weight of the carbide phase, about 15% by weight to about 40% by weight based on the weight of the carbide phase, and about 15% by weight to about 45% by weight based on the weight of the carbide phase. Alternatively, the regenerated non-cemented carbide may be present in any amount up to 100% of the carbide phase.

[0045]

[0046] The cemented carbide compositions disclosed herein have a transverse rupture strength (TRS-B) of at least about ≧3000 MPa as measured according to ISO 3327-2009 standard. Additionally, the cemented carbide compositions may be free of electrochemically processed recycled materials. Alternatively, the resulting cemented carbide may have a transverse rupture strength in the range of about 320 Ksi to about 570 Ksi as measured according to ASTM B 406 standard for a sample containing 100 wt. % recycled unsintered cemented carbide. In some examples, the transverse rupture strength is in the range of about 330 Ksi to about 540 Ksi as measured according to ASTM B 406 standard for a sample containing 90 wt. % zinc recycled carbide and 10 wt. % recycled unsintered carbide. The transverse breaking strength ranges, as measured in accordance with the ASTM B 406 standard, were further demonstrated for compositions defined as 80% by weight recycled zinc carbide and 20% by weight recycled non-sintered carbide, 70% by weight recycled zinc carbide and 30% by weight recycled non-sintered carbide, 60% by weight recycled zinc carbide and 40% by weight recycled non-sintered carbide, 50% by weight recycled zinc carbide and 50% by weight recycled non-sintered carbide, and 45% by weight recycled zinc carbide and 55% by weight recycled non-sintered carbide.

[0046]

[0047] Hardmetal compositions containing the recycled carbide materials described herein exhibit superior mechanical properties, or at a minimum, properties substantially similar to virgin carbide. Thus, there is great flexibility to combine recycled unsintered carbide and recycled zinc carbide with virgin metal binders, grain growth inhibitors, organic binders, and other ingredients to provide new powder compositions for the manufacture of hardmetal parts.

[0047]

[0048] For example, the regenerated non-sintered carbides and regenerated zinc carbides may typically include or consist of tungsten carbide as the carbide material, or alternatively, the regenerated non-sintered carbides and regenerated zinc carbides may include tungsten carbide and at least one or more of a carbide, a boride, a nitride, or a carbonitride of a metal selected from the group consisting of Groups IVB, VB, and VIB of the periodic table.

[0048]

[0049] The regenerated non-sintered carbide and regenerated zinc carbide may exhibit any average particle size not inconsistent with or compatible with the objectives of the present disclosure. In general, the regenerated non-sintered carbide and regenerated zinc carbide of the cemented carbide composition may typically have an average particle size in the range of, for example, 0.5 μm to 30 μm. In certain embodiments, the regenerated non-sintered carbide and regenerated zinc carbide of the sintered carbide composition may have an average particle size in the range of 1 μm to 5 μm, 1 μm to 10 μm, 1 μm to 15 μm, 1 μm to 20 μm, 1 μm to 25 μm, 1 μm to 30 μm, 5 μm to 10 μm, 10 μm to 15 μm, 5 μm to 15 μm, 15 μm to 20 μm, 5 μm to 20 μm, 20 μm to 25 μm, 5 μm to 25 μm, 25 μm to 30 μm, or 5 μm to 30 μm.

[0049]

[0050] To determine particle size, a person skilled in the art can usually use either dynamic digital image analysis (DIA), static laser light scattering (SLS), also known as laser diffraction, or visual measurement by electron microscopy, a technique known as image analysis and light obscuration. Each method covers a characteristic size range that can be measured. These ranges overlap in part. However, the results of measuring the same material may differ depending on the specific method used. A person skilled in the art who wishes to determine particle size or particle size distribution will easily understand how each of the mentioned methods is generally performed and practiced. Thus, the reader is directed, for example, to (i) "Comparison of Methods". For a further understanding of each procedure and methodology, see (ii) Kelly et al., "Graphical comparison of image analysis and laser diffraction particle size analysis data obtained from the measurements of nonspherical particle systems", AAPS PharmSciTech., 2006 Aug 18;Vol.7(3):69. All of these documents are incorporated herein in their entirety.

[0050]

[0051] Cemented carbide and cermet powders of the desired particle size can be produced by subjecting the cemented carbide and cermet powders to a milling operation under ambient conditions (25° C., 298.15 K, 101.325 kPa pressure in a ball mill or attritor mill) for several hours (e.g., 8, 16, 32, 64 hours) using a metal binder during the production of the powder. As will be appreciated by those skilled in the art, milling is performed by first adding a grinding liquid to the powder to form a milled powder slurry composition. The grinding liquid can be water, alcohols such as, but not limited to, ethanol, methanol, isopropanol, butanol, cyclohexanol, organic solvents such as acetone and toluene, alcohol mixtures, alcohol and solvent mixtures, or similar components. The properties of the milled powder slurry composition depend, among other things, on the amount of grinding liquid added. Since drying the milled powder slurry composition requires energy, it is desirable to minimize the amount of grinding liquid used to keep costs down. However, sufficient grinding liquid must be added to achieve a pumpable milled powder slurry composition and avoid clogging of the system. Additionally, other compounds known to those skilled in the art may be added to the slurry, such as dispersants, pH adjusters, etc. Organic binders such as polyethylene glycol (PEG), paraffin, polyvinyl alcohol (PVA), long chain fatty acids, waxes, or any combination thereof, or similar components, may be added to the milled powder slurry composition prior to milling, typically at 15% to 25% by volume of the total volume of the formed slurry, to facilitate the formation of the cemented carbide and metal binder phase powder blend during the milling operation, further function as a pressing agent, and finally, to facilitate handling of the formed green article in the subsequent pressing / molding step described below in paragraph

[0056] .

[0051]

[0052] The primary objective of the milling operation is to promote good metal binder distribution and good wetting between the hard cement carbide constituent particles and the metal binder powder to enhance the physical integrity of the milled powder slurry composition and, in some cases, to deagglomerate the tungsten carbide (WC) crystals.

[0052]

[0053] Acceptable metal binder distribution and good wettability are basic and essential parameters for obtaining a hardmetal material with good physical quality. On the other hand, if the distribution or wettability of the metal binder is too poor, it may result in the formation of undesirable pores and cracks in the final sintered hardmetal body, which will have a negative impact on the produced hardmetal.

[0053]

[0054] The milled powder slurry composition can be spray dried, freeze dried, or vacuum dried to granulate, for example, to provide free-flowing powder agglomerates of various shapes, including spherical. Alternatively, the milled powder slurry composition can be vacuum dried to provide a powder suitable for isostatic pressing to form a green body. In some cases, the regenerated carbide material can be crushed or comminuted prior to milling with the metal binder.

[0054]

[0055] In spray drying, a ground powder slurry composition comprising powdered material and an organic binder mixed with an organic liquid is sprayed through a suitable nozzle in a drying tower where the small droplets are instantly dried by a hot gas stream, for example in a nitrogen stream, to form spherical powder agglomerates exhibiting unrestricted flow properties.

[0055]

[0056] The powders are formed or consolidated into a green article or object in preparation for the sintering process. The green body is formed from the powder blend using conventional techniques such as multi-axis pressing, extrusion, metal injection molding, cold tool pressing techniques including cold isostatic pressing, pill pressing, tape casting, and other methods known in the powder metallurgy art. Any consolidation method not inconsistent with the objectives of the present invention may be utilized. Forming provides green density and / or green strength that facilitates handling and green processing of the powder aggregates since the processed material is in the form of a compressed powder. In one example of the present disclosure, forming is performed by a pressing operation. Here, pressing can be performed by a commonly used uniaxial pressing operation with a force of 5 tons to 40 tons.

[0056]

[0057] The green body may be subjected to a pre-sintering temperature increase treatment in order to completely remove the organic binder. This is described in the following paragraphs.

[0058] The sintering process described further in can be carried out in the same equipment when carrying out the sintering process. Suitable temperatures for removing the organic binder can be employed, typically under a reactive H2 atmosphere, with a H2 flow rate generally between 1000 L / h and 10,000 L / h, for example, at a temperature conventionally increased at a rate of about 0.70°C / min, such as 200°C to 450°C, 200°C to 500°C, 200°C to 600°C, 250°C to 450°C, 250°C to 500°C, 250°C to 600°C, 300°C to 450°C, 300°C to 500, or 300°C to 600°C. In some examples, after removing the organic binder, the temperature is increased to the desired pre-sintering temperature at a rate of about 2°C / min to about 10°C / min, or at a rate of about 2°C / min to about 5°C / min. The temperature is maintained for 1 to 90 minutes until the entire body in the sintering furnace reaches the desired temperature and the desired phase transformation (i.e., removal of the organic binder) is complete. In general, the pre-sintering step can be carried out in a vacuum or in a reactive atmosphere (H2), or in a non-reactive atmosphere such as nitrogen (N2), argon (Ar), etc.

[0057] The pre-sintered and de-bindered green body then undergoes a consolidation process to form the final sintered material, which may typically be carried out using pressures of 50kbar-75kbar, 50kbar-80kbar, 50kbar-85kbar, 50kbar-90kbar, 60kbar-75kbar, 60kbar-80kbar, 60kbar-85kbar, 60kbar-90kbar, 70kbar-75kbar, 70kbar-80kbar, 70kbar-85kbar, or 70kbar-90kbar. However, depending on the composition, this pressure range can drop to a range of 35 kbar to 60 kbar at temperatures ranging from 1300°C to 1500°C, 1300°C to 1600°C, 1300°C to 1700°C, 1300°C to 1800°C, 1400°C to 1500°C, 1400°C to 1600°C, 1400°C to 1700°C, 1400°C to 1800°C, 1500°C to 1600°C, 1500°C to 1700°C, or 1500°C to 1800°C, with residence times at maximum temperature typically being 1 minute to 60 minutes.

[0058]

[0059] The green body can be subjected to either vacuum sintering or sintering under an argon (Ar) or hydrogen atmosphere. In vacuum sintering, the green body is placed in a vacuum furnace and sintered at temperatures generally between about 1300°C to 1500°C, 1300°C to 1600°C, 1300°C to 1700°C, 1300°C to 1800°C, 1400°C to 1500°C, 1400°C to 1600°C, 1400°C to 1700°C, 1400°C to 1800°C, 1500°C to 1600°C, 1500°C to 1700°C, or 1500°C to 1800°C. In some instances, hot isostatic pressing (HIP) may be added to the vacuum sintering process. Hot isostatic pressing (HIP) may be performed as a post-sintering operation or during vacuum sintering, resulting in a sintering HIP process. The resulting sintered cemented carbide articles can exhibit fracture hardness, fracture toughness, and transverse fracture strength values ​​as described herein.

[0059]

[0060] The recycled hard metal material of the hard metal composition may be composed of zinc recycled hard metal, as described above. For example, recycled zinc carbide may be the only species of the recycled powder component. Alternatively, the recycled carbide material may include sintered recycled zinc carbide and sintered hard metal processed by one or more different additional recycling methods, such as, but not limited to, cold stream process, alkaline leaching process, chlorination system, high temperature smelting, etc. The sintered recycled zinc carbide may be mixed with other recycled sintered hard metal materials in amounts consistent with and compatible with the objectives of the present invention. The amount of sintered recycled zinc carbide material in the recycled carbide powder component may be selected according to several considerations, including the desired mechanical and chemical properties of the article formed from the powder.

[0060]

[0061] Alternatively, in some cases, virgin cemented carbide components may be included in addition to further improve the mechanical properties of the cemented carbide composition. The virgin carbide component may include carbides, borides, nitrides, and / or carbonitrides of one or more metals selected from Groups IVB, VB, and VIB of the Periodic Table. Being virgin, the metal carbides, borides, nitrides, and / or carbonitrides have never been part of a sintered carbide composition before and have not been recycled. In some examples, the virgin carbide component may include at least one of tungsten carbide, tantalum carbide, niobium carbide, vanadium carbide, chromium carbide, zirconium carbide, hafnium carbide, or titanium carbide, or any combination thereof. The virgin carbide component may be present in the powder composition in any amount consistent with and compatible with the objectives of the present invention. The amount of the virgin carbide component can be selected according to several considerations, including, but not limited to, the desired mechanical and chemical properties of the sintered article formed from the powder, and the specific compositional identity of the recycled carbide powder component. The virgin carbide component can typically be present in an amount of 0.05% to 20% by weight based on the weight of the carbide phase, such as, for example, 0.1% to 5% by weight, 0.1% to 7% by weight, 0.1% to 10% by weight, 0.1% to 12% by weight, 0.1% to 15% by weight, 0.1% to 17% by weight, or 0.1% to 20% by weight based on the weight of the carbide phase.

[0061]

[0062] The cemented carbide composition may also include at least one or more metal binders and grain growth inhibitors. Non-limiting examples of grain growth inhibitors include carbides such as vanadium carbide (VC), chromium carbide (Cr3C2), tantalum carbide (TaC), titanium carbide (TiC), zirconium carbide (ZrC), and niobium carbide (NbC). The metal binder may include one or more transition metals from Group VIIIB of the periodic table. In certain embodiments, the metal binder may be cobalt, or a cobalt-based alloy. The powdered cobalt-based alloy binder may include a cobalt-transition metal alloy in some specific embodiments. For example, the transition metal of the binder alloy may be suitably selected from the group consisting of molybdenum, ruthenium, rhenium, rhodium, platinum, palladium, manganese, copper, iron, nickel, or combinations thereof. In other particular embodiments, the powdered cobalt-based metallic binder may also contain metalloids such as silicon and / or aluminum.

[0062]

[0063] The metallic binder may be present in the cemented carbide powder composition in any amount not inconsistent or compatible with the objectives of the present invention. The metallic binder may typically be present in an amount of 1 wt% to 30 wt% of the total weight of the cemented carbide powder composition. In some cases, the metallic binder may be present in an amount of 1 wt% to 3 wt% of the total weight of the cemented carbide powder composition. In other examples, the metallic binder may be present in an amount of 1 wt% to 5 wt% of the total weight of the cemented carbide powder composition. In yet other examples, the metallic binder may be present in an amount of 1 wt% to 7 wt% of the total weight of the cemented carbide powder composition. In yet other examples, the metallic binder may be present in an amount of 1 wt% to 10 wt% of the total weight of the cemented carbide powder composition. In a further example, the metallic binder may be present in an amount of 1 wt% to 15 wt% of the total weight of the cemented carbide powder composition. In yet another example, the metallic binder may be present in an amount of 1 wt% to 20 wt% of the total weight of the cemented carbide powder composition. In another embodiment, the metallic binder can be present in an amount of 1 wt% to 25 wt% of the total weight of the cemented carbide powder composition. In yet another embodiment, the metallic binder can be present in an amount of 1 wt% to 27 wt% of the total weight of the cemented carbide powder composition. In certain embodiments, the metallic binder and grain growth inhibitor can be present in an amount of 1 wt% to 2 wt%, 2 wt% to 5 wt%, 5 wt% to 7 wt%, 3 wt% to 7 wt%, or 7 wt% to 10 wt%, 10.1 wt%, 10.2 wt%, 10.3 wt%, 10.4 wt%, 10.5 wt%, 10.6 wt%, 10.7 wt%, 10.8 wt%, or 10.9 wt% of the total weight of the cemented carbide powder composition. The metallic binder coats the carbide component of the cemented carbide composition, including individual particles of the recycled carbide component and the virgin carbide component (if present).

[0063]

[0064] In the case of sintered cemented carbide articles, such sintered cemented carbide articles can be produced from powders of a cemented carbide composition that includes a carbide phase (or carbide material) that generally comprises greater than 70% by weight of the sintered cemented carbide product, recycled cemented carbide material. The carbide phase may alternatively be present in an amount greater than 75% by weight of the sintered cemented carbide article, greater than 80% by weight of the sintered cemented carbide article, greater than 85% by weight of the sintered cemented carbide article, greater than 89% by weight of the sintered cemented carbide article, greater than 90% by weight of the sintered cemented carbide article, greater than 95% by weight of the sintered cemented carbide article, about 70% to about 95% by weight of the sintered cemented carbide article, about 70% to about 90% by weight of the sintered cemented carbide article, about 75% to about 95% by weight of the sintered cemented carbide article, about 70% to about 95% by weight of the sintered cemented carbide article, about 80% to about 95% by weight of the sintered cemented carbide article, about 80% to about 90% by weight of the sintered cemented carbide article, about 85% to about 95% by weight of the sintered cemented carbide article, or about 85% to about 90% by weight of the sintered cemented carbide article.

[0064]

[0065] The carbide phase may include or consist of recycled zinc carbide, recycled unsintered carbide, virgin carbide, ammonium paratungstate treated cemented carbide scrap, among other carbide materials.

[0065]

[0066] The regenerator zinc carbide material may be present in the carbide phase in an amount of about 45% to about 100% by weight based on the weight of the carbide phase, about 45% to about 95% by weight based on the weight of the carbide phase, about 45% to about 90% by weight based on the weight of the carbide phase, about 45% to about 85% by weight based on the weight of the carbide phase, about 45% to about 80% by weight based on the weight of the carbide phase, about 45% to about 75% by weight based on the weight of the carbide phase, about 45% to about 70% by weight based on the weight of the carbide phase, or about 45% to about 65% by weight based on the weight of the carbide phase. % by weight based on the weight of the carbide phase, about 50% by weight to about 100% by weight based on the weight of the carbide phase, about 50% by weight to about 95% by weight based on the weight of the carbide phase, about 50% by weight to about 90% by weight based on the weight of the carbide phase, about 50% by weight to about 85% by weight based on the weight of the carbide phase, about 50% by weight to about 80% by weight based on the weight of the carbide phase, about 50% by weight to about 75 ... 0% to about 70% by weight, about 50% to about 65% by weight based on the weight of the carbide phase, about 55% to about 100% by weight based on the weight of the carbide phase, about 55% to about 95% by weight based on the weight of the carbide phase, about 55% to about 90% by weight based on the weight of the carbide phase, about 55% to about 85% by weight based on the weight of the carbide phase, about 55% to about 80% by weight based on the weight of the carbide phase, about 55% by weight based on the weight of the carbide phase about 75% by weight, about 55% by weight to about 70% by weight based on the weight of the carbide phase, about 55% by weight to about 65% by weight based on the weight of the carbide phase, about 60% by weight to about 100% by weight based on the weight of the carbide phase, about 60% by weight to about 95% by weight based on the weight of the carbide phase, about 60% by weight to about 90% by weight based on the weight of the carbide phase, about 60% by weight to about 85% by weight based on the weight of the carbide phase, about 60% by weight to about 80% by weight based on the weight of the carbide phase %, about 60% to about 75% by weight based on the weight of the carbide phase, about 60% to about 70% by weight based on the weight of the carbide phase, about 55% to about 65% by weight based on the weight of the carbide phase, about 60% to about 100% by weight based on the weight of the carbide phase, about 60% to about 95% by weight based on the weight of the carbide phase, about 60% to about 90% by weight based on the weight of the carbide phase, about 60% to about 85% by weight based on the weight of the carbide phase,about 60% by weight to about 80% by weight based on the weight of the carbide phase, about 60% by weight to about 75% by weight based on the weight of the carbide phase, about 60% by weight to about 70% by weight based on the weight of the carbide phase, about 60% by weight to about 65% by weight based on the weight of the carbide phase, about 70% by weight to about 100% by weight based on the weight of the carbide phase, about 70% by weight to about 95% by weight based on the weight of the carbide phase, about 70% by weight to about 90% by weight based on the weight of the carbide phase, about 70% by weight to about 85% by weight based on the weight of the carbide phase, about 70% by weight to about 80% by weight based on the weight of the carbide phase, about 70% by weight to about 70% by weight based on the weight of the carbide phase 5% by weight, about 75% to about 100% by weight based on the weight of the carbide phase, about 75% to about 95% by weight based on the weight of the carbide phase, about 75% to about 90% by weight based on the weight of the carbide phase, about 75% to about 85% by weight based on the weight of the carbide phase, about 75% to about 80% by weight based on the weight of the carbide phase, about 80% to about 100% by weight based on the weight of the carbide phase, about 80% to about 95% by weight based on the weight of the carbide phase, about 80% to about 90% by weight based on the weight of the carbide phase, or about 80% to about 85% by weight based on the weight of the carbide phase.

[0066]

[0067] The regenerated non-sintered carbide material may have, in the carbide phase, about 0% to about 10% by weight based on the weight of the carbide phase, about 0% to about 20% by weight based on the weight of the carbide phase, about 0% to about 30% by weight based on the weight of the carbide phase, about 0% to about 35% by weight based on the weight of the carbide phase, about 0% to about 40% by weight based on the weight of the carbide phase, about 0% to about 45% by weight based on the weight of the carbide phase, about 5% to about 10% by weight based on the weight of the carbide phase, about 5% to about 20% by weight based on the weight of the carbide phase, about 5% to about 30% by weight based on the weight of the carbide phase, about 5% to about 35% by weight based on the weight of the carbide phase, about 5% to about 40% by weight based on the weight of the carbide phase. %, about 5% to about 45% by weight based on the weight of the carbide phase, about 10% to about 20% by weight based on the weight of the carbide phase, about 10% to about 30% by weight based on the weight of the carbide phase, about 10% to about 35% by weight based on the weight of the carbide phase, about 10% to about 40% by weight based on the weight of the carbide phase, about 10% to about 45% by weight based on the weight of the carbide phase, about 15% to about 20% by weight based on the weight of the carbide phase, about 15% to about 30% by weight based on the weight of the carbide phase, about 15% to about 35% by weight based on the weight of the carbide phase, about 15% to about 40% by weight based on the weight of the carbide phase, about 15% to about 45% by weight based on the weight of the carbide phase. Alternatively, the regenerated non-sintered carbide may be present in any amount of the carbide phase up to 100%.

[0067]

[0068] Additionally, the reclaimed non-sintered carbide and reclaimed zinc carbide of the cemented carbide article may exhibit any average grain size consistent with or in accordance with the objectives of the present disclosure. In general, the reclaimed non-sintered carbide and reclaimed zinc carbide of the cemented carbide article may typically have an average grain size in the range of, for example, 0.5 μm to 30 μm. In certain embodiments, the regenerated zinc carbide of the regenerated non-sintered carbide and sintered carbide articles may have an average particle size in the range of 1 μm to 5 μm, 1 μm to 10 μm, 1 μm to 15 μm, 1 μm to 20 μm, 1 μm to 25 μm, 1 μm to 30 μm, 5 μm to 10 μm, 10 μm to 15 μm, 5 μm to 15 μm, 15 μm to 20 μm, 5 μm to 20 μm, 20 μm to 25 μm, 5 μm to 25 μm, 25 μm to 30 μm, or 5 μm to 30 μm.

[0068]

[0069] As mentioned above, to determine particle size, one skilled in the art can typically use methodologies such as dynamic digital image analysis (DIA), static laser light scattering (SLS), or visual measurement by electron microscopy.

[0069]

[0070] Sintered cemented carbide articles using the recycled carbide powders described herein exhibit superior mechanical properties or, at a minimum, substantially equivalent to sinters formed solely from virgin carbide powder compositions, in particular sintered cement products having a transverse rupture strength (TRS-B) of at least about ≧3000 MPa as measured according to ISO 3327-2009. Alternatively, the resulting cemented carbide may have a transverse rupture strength in the range of about 320 Ksi to about 570 Ksi as measured according to ASTM B 406 for samples containing 100% by weight recycled unsintered cemented carbide. In some examples, the transverse rupture strength is in the range of about 330 Ksi to about 540 Ksi as measured according to ASTM B 406 for samples containing 90% by weight zinc recycled carbide and 10% by weight recycled unsintered carbide. Transverse breaking strength ranges, as measured in accordance with the ASTM B 406 standard, were also obtained for compositions specified as at least 80% by weight recycled zinc carbide and 20% by weight recycled non-sintered carbide, 70% by weight recycled zinc carbide and 30% by weight recycled non-sintered carbide, 60% by weight recycled zinc carbide and 40% by weight recycled non-sintered carbide, 50% by weight recycled zinc carbide and 50% by weight recycled non-sintered carbide, and 45% by weight recycled zinc carbide and 55% by weight recycled non-sintered carbide.

[0070]

[0071] Furthermore, the sintered cemented carbide article has a compressibility of, for example, 11 g / cm 3 ~15g / cm 3 , 12g / cm 3 ~15g / cm 3 , 13g / cm 3 ~15g / cm 3 , 14g / cm 3 ~15g / cm 3In addition, the sintered hardmetal articles described herein can be free or substantially free of lower carbide materials, including eta-materials [(CoW)C], W2C, and / or W3C. In some embodiments, the sintered hardmetal articles described herein can be free of at least one of type A porosity and type B porosity. Furthermore, in certain embodiments, the sintered hardmetal articles described herein can be further free of free graphite (type C porosity).

[0071]

[0072] The sintered cemented carbide products and hardmetal compositions described herein can be advantageously incorporated as cutting elements or as components of cutting elements for a variety of applications. In some embodiments, the sintered cemented carbide products and hardmetal compositions can include cutting inserts for machining metals and / or metal alloys. In other embodiments, the sintered cemented carbide products and hardmetal compositions can include interrupted cutting tools, such as drills, end mills, and / or milling inserts.

[0072]

[0073] Additionally, the sintered cemented carbide articles described herein can be combined with what is known in the art as superabrasive ultrahard materials, including, but not limited to, single crystal diamond, polycrystalline diamond (PCD), thermally stable polycrystalline diamond (PCD), chemical vapor deposition (CVD) diamond, metal matrix diamond composites, ceramic matrix diamond composites, nanodiamond, cubic boron nitride (cBN), polycrystalline cubic boron nitride (PCBN). For example, the sintered cemented carbide articles described herein can structurally act as an anchor substrate or support to enhance functionality, whereby the superabrasive is sintered in a high temperature, high pressure (HTHP) process.

[0073]

[0074] In such a scenario, the layer of ultra-abrasive hard material can provide increased wear resistance and extend the life of cutting elements and / or wear parts that utilize the sintered hardmetal compositions that make up the hardmetal products described herein. In some particular embodiments, the sintered hardmetal articles can be used in the manufacture of drilling tools, rotary tools, or cutting tools, for example as wear parts such as wire drawing dies, or in drilling and mining equipment incorporating drilling bodies, drill bits, and cutters.

[0074]

[0075] The sintered cemented carbide articles or cemented carbide powder compositions having the unique mechanical properties described herein may be coated with one or more refractory materials. As used herein, refractory materials refer to materials that are resistant to decomposition by heat, pressure, or chemical attack. The coating may be performed by physical vapor deposition (PVD) or chemical vapor deposition (CVD) of one or more elements selected from aluminum, metallic elements of groups IVB, VB, and VIB of the periodic table, and one or more elements selected from groups IIIA, IVA, VA, and VIA of the periodic table. For example, the refractory coating may include one or more carbides, nitrides, carbonitrides, oxides, or borides of one or more metallic elements selected from aluminum, metallic elements of groups IVB, VB, and VIB of the periodic table. Furthermore, the coating may suitably be a single layer coating or a multi-layer coating. When a refractory material is used, its weight may be present up to 10% by weight. In some examples, the fire resistant material is present at 1% to 2% by weight, 1% to 3% by weight, 1% to 4% by weight, 3% to 4% by weight, 3% to 5% by weight, 3% to 6% by weight, 5% to 6% by weight, 5% to 7% by weight, 5% to 8% by weight, or 5% to 10% by weight. EXAMPLES

[0075] Working Example

[0076] The following examples are presented to provide those of ordinary skill in the art with a complete disclosure and description of how to make and use the described subject matter, and are not intended to limit the scope of what the inventors regard as their disclosure, nor are they intended to represent that the following experiments are all or the only experiments performed. Efforts have been made to ensure accuracy with respect to numbers used, but some experimental error and deviation should be accounted for. Unless otherwise indicated, parts are by weight, molecular weight is weight average molecular weight, temperature is in degrees Celsius, and pressure is at or near atmospheric.

[0076] Example 1

[0077] The recycled carbide material is composed of a composite of zinc and recycled carbide and / or recycled unsintered carbide and exhibits superior mechanical properties of hardness, fracture toughness, and transverse fracture strength compared to sintered carbide containing only virgin raw materials.

[0077]

[0078] In accordance with the subject matter described herein, a hardmetal composition was prepared. The hardmetal composition includes at least 70 wt. % recycled carbide material, of which 45 wt. % to 100 wt. % is recycled zinc carbide. A reference comparative composition was also prepared, consisting of 10 wt. % Co and 90 wt. % virgin WC. As shown in Figures 1A and 1B, the hardmetal composition according to the present subject matter surprisingly exhibits superior, or at least substantially equivalent, hardness and fracture toughness properties when compared to the reference hardmetal (i.e., rounded tip).

[0078]

[0079] 1A and 1B show the measured mechanical properties of (I) a reference material consisting of 10 wt. % Co and 90 wt. % virgin WC, and (II) a material according to an embodiment of the present inventive subject matter (composed of at least 70 wt. % recycled carbide material, the recycled carbide being composed of a combination of recycled zinc carbide and recycled non-sintered carbide).

[0079]

[0080] The recycled zinc carbide was mixed in combination with recycled unsintered carbide in amounts ranging from 0% to 50% by weight of the total weight of the cemented carbide composition.lc ) (FIG. 1A) was measured according to the ISO 28079-2009 standard. The transverse breaking strength TRS-A (FIG. 1B) was measured according to the ISO 3327-2009 standard and then converted to a transverse breaking strength TRS-B value by applying a multiplier of 1.15 as described in paragraph

[0032] of this disclosure.

[0080]

[0081] In Figures 1A and 1B, the X-axis shows the total weight percent composition of the zinc recycled carbide and the recycled non-sintered carbide (i.e., using the recycled non-sintered carbide and the remaining zinc recycled carbide as the balance to add up to 100 weight percent), while the Y-axis in Figure 1A shows the measured (I) hardness, HV30 (dotted graph in Figure 1A), (II) fracture toughness, K lc (FIG. 1A, dashed line graph), and (III) transverse breaking strength TRS-B (FIG. 1B, dashed line graph).

[0081]

[0082] As is evident from Figures 1A and 1B, materials consisting of at least 70 wt% recycled carbide material, of which 45 wt% to 100 wt% is zinc recycled carbide, have a hardness HV30 and fracture toughness K when compared to a reference material consisting of 10 wt% Co and 90 wt% WC containing only virgin raw materials. lc The mechanical properties characterized by (e.g., taking into account the standard deviation) are better than or at least substantially equivalent to (i.e., the upper round point indicates hardness HV30 and the lower round point indicates fracture toughness K lc Furthermore, the addition of up to 50 wt. % recycled unsintered carbide to the mixture significantly imparts to the zinc recycled carbide a robust and advantageous combination of hardness, fracture toughness, and TRS-B value of at least about ≧3000 MPa as measured according to the ISO 3327-2009 standard.

[0082]

[0083] Additionally, transverse rupture strength was also measured in accordance with ASTM B 406 standard and reported in Ksi as shown in Table 1 below. Table 1 shows the minimum, maximum and average transverse rupture strength measured in Ksi in accordance with ASTM B 406 standard for (i) a reference material comprised of 10 wt% Co and 90 wt% virgin WC, and (ii) a recycled carbide material comprised of composite recycled zinc carbide and / or recycled non-sintered carbide (i.e., Composition A and Composition B). Composition A contained only 100 wt% recycled non-sintered carbide, and the value obtained for composition A in Table 1 below is the average of multiple compositions containing only 100 wt% recycled non-sintered carbide. Composition B contained 90 wt% recycled zinc carbide and 10 wt% recycled non-sintered carbide. As shown in Table 1, the average transverse fracture strength value determined according to the ASTM B 406 standard for the material defined as composition A containing only 100 wt. % recycled unsintered carbide was 462 Ksi. This was comparable to the average value of 473 Ksi obtained for the reference material composed of 10 wt. % Co and 90 wt. % virgin WC. The recycled cemented carbide materials disclosed herein had transverse fracture strengths measured according to the ASTM B 406 standard ranging from about 328 Ksi to about 543 Ksi for composition B and from about 320 Ksi to about 571 Ksi for composition A.

[0083] TIFF2025503741000001.tif39170

[0084]

[0085] While the present disclosure has been described in relation to embodiments, those skilled in the art will appreciate that additions, deletions, modifications, and substitutions not specifically described may be made without departing from the spirit and scope of the present disclosure, as defined in the appended claims.

[0085]

[0086] With respect to the use of substantially any plural and / or singular terms herein, one of ordinary skill in the art can translate from plural to singular and / or from singular to plural as appropriate to the context and / or application. For clarity, the various permutations of singular / plural have not been explicitly set forth herein.

[0086]

[0087] The subject matter described herein may depict different components contained within or connected to different other components. It should be understood that the architectures depicted are merely exemplary and that in fact many other architectures that achieve the same functionality may be implemented. Conceptually, an arrangement of components to achieve the same functionality is effectively "associated" such that a desired functionality is achieved. Thus, any two components combined herein to achieve a particular functionality may be considered to be "associated" with each other such that the desired functionality is achieved, regardless of the architecture or intermediate components. Similarly, any two components so associated may also be considered to be "operably connected" or "operably coupled" with each other to achieve a desired functionality, and any two components that may be so associated may also be considered to be "operably coupleable" with each other to achieve a desired functionality. Specific examples of operably coupleable include, but are not limited to, physically coupleable and / or physically interacting components, and / or wirelessly interactable and / or wirelessly interacting components, and / or logically interacting and / or logically interacting components.

[0087]

[0088] In some cases, one or more components may be referred to herein as being "configured to," "configured by," "configurable to," "operable / operative to," "adapted / adaptable," "able to," "conformable / conformed to," and the like. Those skilled in the art will appreciate that, unless the context requires otherwise, such terms (e.g., "configured to") can generally encompass active and / or inactive and / or standby components.

[0088]

[0089] While certain aspects of the subject matter described herein have been shown and described, it will be apparent to one skilled in the art that, based on the teachings herein, changes and modifications may be made without departing from the subject matter described herein and its broader aspects, and therefore, the appended claims are intended to encompass within their scope all changes and modifications that are within the true spirit and scope of the subject matter described herein. In general, those skilled in the art will understand that the terms used in this specification, and particularly in the appended claims (e.g., the body of the appended claims), are generally intended as "open" terms (e.g., the term "including" should be interpreted as "including but not limited to," the term "having" should be interpreted as "having at least," the term "includes" should be interpreted as "includes but is not limited to," etc.). Furthermore, those skilled in the art will understand that if a specific number of claims are intended to be included, such intent will be explicitly stated in the claims, and in the absence of such recitation, no such intent exists. For example, to aid in understanding, the following appended claims may use the introductory phrases "at least one" and "one or more" to introduce the claim recitation.However, the use of such phrases should not be construed to mean that the introduction of a claim statement by the indefinite article "a" or "an" limits a particular claim that includes such an introduced claim statement to claims that contain only one such statement, even when the same claim includes the introduced phrases "one or more" or "at least one" and the indefinite article "a" or "an" (e.g., "a" and / or "an" should generally be construed to mean "at least one" or "one or more"). The same applies to the use of definite articles used to introduce claim statements.

[0089]

[0090] Further, even if a particular number of introduced claims is explicitly recited, one of ordinary skill in the art will recognize that such a recitation should typically be interpreted to mean at least the recited number (e.g., the mere recitation of "two recitations" without other modifiers typically means at least two recitations, or more than two recitations).

[0090]

[0091] Furthermore, when a convention similar to "at least one of A, B, C, etc." is used, such a configuration is generally intended in the sense that one of ordinary skill in the art would understand the convention (e.g., "a system including at least one of A, B, C" includes, but is not limited to, systems including only A, only B, only C, A and B together, A and C together, B and C together, and / or A, B, C together, etc.). When a convention similar to "at least one of A, B, C, etc." is used, such a configuration is generally intended in the sense that one of ordinary skill in the art would understand the convention (e.g., "a system including at least one of A, B, C" includes, but is not limited to, systems including only A, only B, only C, A and B together, A and C together, B and C together, and / or A, B, C together, etc.).

[0091] Moreover, those skilled in the art will appreciate that whether in this specification, claims, or drawings, separating words and / or phrases presenting two or more alternative terms should be understood as contemplating the possibility of including one of the terms, either term, or both terms, unless the context dictates otherwise. For example, the phrase "A or B" is typically understood to include the possibilities of "A" or "B" or "A and B."

[0092]

[0093] With respect to the appended claims, those skilled in the art will appreciate that the operations described therein may generally be performed in any order. Additionally, while various operational flows are depicted in a sequential order, it will be understood that various operations may be performed in orders other than those depicted, or may be performed simultaneously. Examples of such alternative orders include overlapping, alternating, interrupted, reordered, incremental, preparatory, supplemental, simultaneous, reversed, or other variant orders, unless the context dictates otherwise. Additionally, terms such as "responsive to," "related to," and other past tense adjectives are not generally intended to exclude such variants, unless the context dictates otherwise.

[0093]

[0094] Those skilled in the art will appreciate that the specific example processes and / or devices and / or techniques described above are representative of more general processes and / or devices and / or techniques that are taught elsewhere herein, such as in the claims appended hereto and / or elsewhere in this application.

[0094]

[0095] While various aspects and embodiments have been disclosed herein, other aspects and embodiments will be apparent to those of ordinary skill in the art. The various aspects and embodiments disclosed herein are intended to be illustrative and not limiting, with the true scope and spirit being indicated by the following claims.

[0095]

[0096] The illustrative embodiments described in the detailed description, drawings, and claims are not intended to be limiting, as other embodiments may be utilized, and other changes may be made, without departing from the spirit or scope of the subject matter presented here.

[0096]

[0097] Where a range of values ​​is presented, unless the context clearly dictates otherwise, it is understood that each intervening value between the upper and lower limit of that range (to the nearest tenth of the lower limit), and any other stated or intervening value in that presented range, is included in the disclosure. The upper and lower limits of these smaller ranges that may be independently included in the smaller ranges are also included within the scope of the disclosure, unless a specifically excluded limit is stated in the range. When one or both limits are included in the stated range, ranges excluding either both of those included limits are also included in the disclosure.

[0097]

[0098] Those skilled in the art will appreciate that the components (e.g., operations), devices, objects, and the accompanying description described herein are used as examples for conceptual clarity, and that various configuration variations are contemplated. Thus, the specific examples used herein and the accompanying description are intended to be representative of a more general class. In general, the use of a specific example is intended to be representative of the class, and the absence of a particular component (e.g., operation), device, or object should not be construed as a limitation.

[0098]

[0099] Further, for example, sequences and / or chronological ordering of sequences of the systems and methods described herein are illustrative and should not be construed as limiting in nature. Thus, while process steps may be shown and described in a sequential or chronological order, it should be understood that they are not necessarily limited to being performed in a particular order or sequence. For example, steps in such processes or methods may generally be performed in a variety of different sequences and orders within the scope of the present disclosure.

[0099]

[0100] Finally, the published applications and / or patents discussed herein are provided solely for their disclosure prior to the filing dates of the disclosures described, and nothing herein should be construed as an admission that the disclosed disclosures are not entitled to antedate such publication by virtue of prior disclosure.

Claims

1. 1. A hard metal composition comprising: a carbide phase comprising about 45% to about 100% by weight of regenerated zinc carbide, the carbide phase being present in an amount of at least 70% by weight of the hardmetal composition; Binder phase and Including, A cemented carbide composition having a transverse rupture strength, as measured by ASTM B 406 standard, in the range of about 330 Ksi to about 540 Ksi.

2. 10. The cemented carbide composition of claim 1, wherein the carbide phase further comprises regenerated uncemented carbides.

3. 10. The cemented carbide composition of claim 1, wherein the carbide phase is present in an amount of at least 80% by weight of the cemented carbide composition.

4. The cemented carbide composition of claim 1 , wherein the carbide phase is present in an amount of about 89% to about 99% by weight of the cemented carbide composition.

5. 10. The hardmetal composition of claim 1, which is free of electrochemically processed recycled hardmetal material.

6. 10. The cemented carbide composition of claim 1, wherein the regenerator zinc carbide comprises tungsten carbide.

7. 3. The cemented carbide composition of claim 2, wherein the regenerator non-cemented carbide comprises tungsten carbide.

8. The cemented carbide composition of claim 1 , wherein the binder phase comprises a metallic binder.

9. The cemented carbide composition of claim 8 , wherein the metallic binder comprises Co.

10. The cemented carbide composition of claim 1 , wherein the binder phase is present in an amount of about 1% to about 11% by weight of the cemented carbide composition.

11. 1. A method for producing a sintered cemented carbide article, comprising the steps of: a carbide phase comprising about 45% to about 100% by weight of regenerated zinc carbide, the carbide phase being present in an amount of at least 70% by weight of the carbide composition; and Binder phase containing metal binder providing a hardmetal composition comprising: subjecting the carbide composition to a grinding operation to form a powder blend; subjecting the powder blend to a molding operation to form a green body; subjecting the green body to a sintering operation to form a sintered cemented carbide article. Including, The method, wherein the sintered cemented carbide article has a transverse rupture strength, as measured by ASTM B 406 standard, in the range of about 330 Ksi to about 540 Ksi.

12. The method of claim 11 , wherein the carbide phase further comprises regenerated uncemented carbide.

13. The method of claim 11 , wherein the carbide phase is present in an amount of at least 80% by weight of the cemented carbide composition.

14. The method of claim 11, wherein the carbide phase is present in an amount of about 89% to about 99% by weight of the cemented carbide composition.

15. 12. The method of claim 11, which does not include electrochemically treated ultrahard recycled materials.

16. 12. The method of claim 11, wherein the regenerated zinc carbide comprises tungsten carbide.

17. The method of claim 12 , wherein the regenerated non-cemented carbide comprises tungsten carbide.

18. The method of claim 11 , wherein the binder phase comprises a metal binder.

19. The method of claim 18 , wherein the metallic binder comprises Co.

20. The method of claim 11, wherein the binder phase is present in an amount of about 1% to about 11% by weight of the hardmetal composition.

21. A cutting tool comprising the cemented carbide composition of claim 1.

Citation Information

Patent Citations

  • Cemented carbide, its production and cemented carbide tool

    JP1999335769A

  • Method for manufacturing pellet for metal powder injection molding

    JP2004002986A

  • Method of recovering metal powder from platinum paste, and method of reproducing platinum paste

    JP2015183199A

  • Manufacturing method for cemented carbide

    JP2015503034A

  • Metal additive manufacturing device and metal additive manufacturing method

    WO2020045383A1